A computer vision framework to detect, track and identify objects in a wide field-of-view airport-airside environment - Thai, Van Phat (Nanyang Technological University, 2023)
To accommodate the steady growth of air traffic, airports worldwide need to increase their capacity by expanding infrastructure and optimizing air traffic procedures. However, as airports add new infrastructure (runways, taxiways, and aprons) into operation, they also increase the challenge of airport airside management. This may lead to an increase in controller workload as well as runway and taxiway incursion events. This problem is compounded by unauthorized access to the control zone by unauthorized and non-cooperative objects, such as drones. Air traffic controllers now are therefore required to monitor more traffic and direct complex operations. For effective airport airside management, controllers must detect aircraft movement on the ground. They also must coordinate push-back procedures, taxiway routing, and runway sequencing for effective airside traffic circulation. Controllers are traditionally located in a tall control tower to manage air traffic through an out-of-window view. Although physical towers have served airside control well, they have several limitations. First, a physical tower is costly for a small airport because the fixed costs for providing air traffic service are independent of the traffic. Secondly, one physical tower might not be sufficient to visually cover a large airport. For full visual traffic coverage of a large airport, the geometric height of a tower can be sustainably high which poses an obstruction to navigation in the airport control zone.